Digital portrait of state and variability for the ice cover of Japan Sea - S. I. Kislova; V. V. Plotnikov; V. A. Dubina (Известия ТИНРО, 2020)
Seasonal and long-term variability of the ice age and concentration in the Japan Sea is analyzed on the base of all available information for 1960–2019. The highest variability of ice concentration is localized in the area with concentration 7–8 points (70–80 %) and follows to shifts of this area: form north to south in early winter and back to the north in late winter. The highest variability of ice age is associated with the area of young ice (age 1–3 points), where influence of melting or freezing on the ice thickness is the greatest. The areas of in-phase and out-phase variability of the ice age and concentration are identified and compared by analysis of standard deviations and 3 the first eigenvectors for restored mid-month fields of ice cover in December-May. Contributions of 3 the first empirical orthogonal functions (EOF) to total variability of the ice cover are determined. Cyclics with periods of 9–12, 2–4, and sometimes 15–16 and 4–6 years are found in variation of EOFs for the ice age and concentration; besides, the 5–7 years periodicity occurs in the ice age spectra for December, January and April.